2015
DOI: 10.1021/jacs.5b02987
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplexed NMR-Reporter Approach to Measure Cellular Kinase and Phosphatase Activities in Real-Time

Abstract: Cell signaling is governed by dynamic changes in kinase and phosphatase activities, which are difficult to assess with discontinuous readout methods. Here, we introduce an NMR-based reporter approach to directly identify active kinases and phosphatases in complex physiological environments such as cell lysates and to measure their individual activities in a semicontinuous fashion. Multiplexed NMR profiling of reporter phosphorylation states provides unique advantages for kinase inhibitor studies and reveals re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015). With this approach the efficacy of kinase drugs can be studied for many kinase targets simultaneously and also under near-cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015). With this approach the efficacy of kinase drugs can be studied for many kinase targets simultaneously and also under near-cellular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution NMR is an ideal technique for characterization of chemical modifications of proteins at the residue level, and has been shown to be particularly suited for monitoring protein phosphorylation events. [40][41][42] Using time-resolved in vitro NMR, we unambiguously identified four serine phosphorylation sites, which react with CK2 at different rates, in NS5A-D3. [38,39] Moreover,f ast NMR experimentsa cquiredw ith sensitivee quipment allow protein phosphorylation eventst ob em onitored in real time, including in intact cells and extracts.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] Moreover,f ast NMR experimentsa cquiredw ith sensitivee quipment allow protein phosphorylation eventst ob em onitored in real time, including in intact cells and extracts. [40][41][42] Using time-resolved in vitro NMR, we unambiguously identified four serine phosphorylation sites, which react with CK2 at different rates, in NS5A-D3. Interestingly, some sites do not have a" canonical" CK2 recognition motif, and had not been predicted previously.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dose et al [ 425 ] used acetylation- and deacetylation-based assays to monitor the activity of histone deacetylase and acetyl-transferase. Thongwichian et al [ 426 ] used peptide-based reporters to identify active kinases and phosphatases in cellular conditions. Lastly, Doura et al [ 427 ] designed a 19 F probe that operates in biological conditions in order to study the adherence and dynamics of proteins found in human blood.…”
Section: In-cell Nmr Approachesmentioning
confidence: 99%